The health effects of universal early childhood interventions: Evidence from Sure Start - Sarah Cattan; Gabriella Conti; Christine Farquharson; Rita Ginja; Maud Pecher (Institute for Fiscal Studies (IFS), 2021)
This paper evaluates the short- and medium-term health impacts of offering families with children under 5 universal access to centres providing childcare, health services, parenting support and parental job assistance. Increased access to these centres during early childhood increases the probability of hospitalisation for infants in the local area. As children age this effect turns negative and grows larger through primary and secondary school. The impacts are concentrated among boys from the poorest areas. The reductions in hospitalisations are driven by reduced infections, injuries, and mental health. The impacts during post-childcare age sug-gest that operating mechanisms are stronger immune systems, safer parenting practices and home environments, and improved emotional and behavioural development among children.
Keywords: I10; I14; I18; 330